The CIRCULATE Trial: Circulating Tumor DNA Based Decision for Adjuvant Treatment in Colon Cancer Stage II Evaluation (AIO-KRK-0217) - Folprecht, Gunnar; Reinacher-Schick, Anke; Weitz, Jürgen; Lugnier, Celine; Kraeft, Anna-Lena; Wisser, Sarah; Aust, Daniela E.; Weiss, Lukas; von Bubnoff, Nikolas; Kramer, Michael; Thiede, Christian; Tannapfel, Andrea (Clinical colorectal cancer, 2022)
Guidance regarding adjuvant treatment decisions in stage II colorectal cancer (CRC) remains uncertain due to lack of predictive clinical or molecular markers. Recently, postoperative circulating tumour (ct)DNA has been demonstrated to be a strong prognostic marker in early colon cancer. CIRCULATE enrols patients with stage II microsatellite stable CRC in Germany (AIO) and Austria (ABCSG). Within the AIO, screening is supported by ColoPredict Plus 2.0, a molecular registry, and screening platform for interventional trials. Patient-specific mutations are centrally analysed by next generation sequencing in the resected primary tumour. A postoperative plasma sample is subsequently screened for the specific mutation(s). ctDNA positive (ctDNApos) patients are randomised (2:1) chemotherapy (capecitabine, oxaliplatin added an investigator's choice) or to follow-up (control group). ctDNA negative (ctDNAneg) patients are randomised (1:4) to be followed-up within CIRCULATE (control group) or outside the trial. Patients in the control group remain blinded to the ctDNA results. The primary objective is to compare disease free survival (DFS) of ctDNApos patients with chemotherapy or control. To demonstrate a treatment effect with a hazard ratio of 0.617 (3-year DFS rates 42.5% vs. 25%), 231 ctDNApos and estimated 2079 ctDNAneg patients are randomised. Secondary aims include to compare overall survival and DFS in the ctDNApos and ctDNAneg patient cohorts and ctDNA kinetics. The CIRCULATE trial may establish ctDNA for adjuvant treatment decision in stage II colon cancer – and with the secondary objectives – support a ctDNA guided follow up in colon cancer stage II and beyond. Circulating tumour DNA (ctDNA) is a prognostic biomarker of recurrence in patients with early stage and resected colorectal cancer. The CIRCULATE study evaluates the predictive value of ctDNA with respect to adjuvant treatment in colon cancer stage II. In total, 231 patients with detectable ctDNA (ctDNApos) post resection are randomised 2:1 to chemotherapy or to control (follow-up). Patients without detectable ctDNA (approx. 2079 patients) are randomized 1:4 into control or off-study. The primary endpoint is the disease-free survival.